Constructing interconnected nanofibers@ZIF-67 superstructure in nafion membranes for accelerating proton transport and confining methanol permeation. (11th November 2021) - Ju, Jingge; Shi, Jiali; Wang, Meng; Wang, Liyuan; Cheng, Bowen; Yu, Xixi; Cai, Yinghui; Wang, Shuaishuai; Fang, Libin; Kang, Weimin
Abstract: A high-performance proton exchange membrane was successfully prepared by incorporating an interconnected PMIA nanofiber@ZIF-8 network (ZHNFs) into Nafion solution, in which the unique ZHNFs were fabricated via in-situ growth of ZIF-67 on the surface of hierarchical PMIA nanofibers (HNFs) with multiscale nanofibers and high hydrophilicity. The hybrid membrane presents an outstanding performance with a peak proton conductivity of 0.277 S cm −1 at 80 °C, 100RH% and a decreased methanol permeability of 1.415 × 10 −7 cm 2 s −1, implying a promising application in direct methanol fuel cells. The superior performance of the membranes could be due to the interconnected structure, high specific surface area of 122.637 m 2 g −1 and active chemical bond of (−N–H) of ZHNFs. Specifically, the 3D interconnected structure of ZHNFs provides consecutive conduction path for protons, ensuring the improvement of proton conductivity. The effective interfacial acid-base pairs (−N–H … −SO3 H) formed via the tight interactions between the –N–H bonds in ZHNFs and –SO3 H groups in Nafion matrix could effectively ameliorate the compatibility of the nanofiber fillers and Nafion matrix, further promoting the methanol barrier of the hybrid membranes. Moreover, the generated acid-base pairs are beneficial for the efficient and rapid proton transfer via providing abundant proton conducting sites. Highlights: Interconnected PMIA nanofiber@ZIF-8 network was obtained. Hierarchical proton-conducting channels and hindered methanol penetration routs were simultaneously achieved. Proton conductivity was highly of 0.277 S cm −1 at 80 °C, 100 RH%.